(untitled) (International Journal of Engineering and Computer Science, 2017)
Today’s life there is a huge demand of storing the information which is available in newspaper as well as in a paper documents format into a computer. So there is a one simple way to store the information of the newspaper into computer system for that first we have to scan the paper then we can store as well as we can also do the some changes as per the requirement. It is based on the basically mobile quality, paper quality and quality of images. Image processing is one of the most growing field in research and technology in today’s world. Detection of text from the images and identification of characters is a challenging problem. Image content can be divided into two types: Which contain attributes like texture, shape and other is in the form of text. It is a little bit challenging task to detect the text from the captured images.